Effect of folic acid on the postharvest physiology of broccoli during storage. (1st March 2021) - Xu, Dongying; Zuo, Jinhua; Fang, Yalin; Yan, Zhicheng; Shi, Junyan; Gao, Lipu; Wang, Qing; Jiang, Aili
Highlights: Folic acid maintained the appearance quality and nutrient levels in broccoli. Folic acid enhanced the antioxidant capacity, resulting in reduced membrane damage. Folic acid delayed the florets yellowing by the regulation of chlorophyll metabolism. Abstract: The objective of the present study was to explore the effect of folic acid on the postharvest physiology of broccoli placed in storage. Broccoli heads were immersed in 5 mg L −1 folic acid for 10 min, then stored at 20 ± 1 °C for 4 days. Results indicated that the postharvest treatment of broccoli with folic acid decreased the rate of flower opening and yellowing, inhibited weight loss, reduced the level of respiration, as well as ethylene generation. Folic acid-treated broccoli maintained their level of chlorophyll, total soluble solids, vitamin C, total phenolics, flavonoids, glucosinolate, and folic acid. Treated broccoli also exhibited reduced accumulation of malondialdehyde (MDA) and reactive oxygen species (ROS). Concomitantly, antioxidant enzyme activity and corresponding gene expression were also enhanced. In contrast, chlorophyll-degrading enzyme gene expression was suppressed. These results indicated that folic acid treatment of broccoli could be used to prolong shelf-life.